BMT210- Microbial Physiology (Fisiologi Mikrob) - PPSKJ, Pusat Pengajian Sains Kajihayat (Pusat Pengajian Sains Kajihayat, 2024)
First Semester Examination 2023/2024 Academic Session February 2024 BMT21 0- Microbial Physiology (Fisiologi Mikrob) Duration: 2 hours (Masa : 2 jam)